Adverse Events of Trivalent Influenza Vaccine among Health Care Workers in Iran - M Hajiabdolbaghi; S Jafari; AR Esteghamati; MN Dadras; MM Gouya; S Jam; H Emadi Koochak; P Kheirandish; S Shahriari; B Moradmand Badie (Tehran University of Medical Sciences, 2009)
"nBackground: To assess the frequency and type of adverse events after influenza vaccination in Iranian adults."nMethods: Health care workers in 7 medical centers received the influenza vaccine from October 2006 to February 2007 and followed by phone regarding symptoms experienced after vaccination."nResults: Of 897 adults who participated in the study, local and systemic reactions were reported by 187 (20.8%) and 198 (22.1%) persons, respectively. The most common local reaction was pain (20.2%), while myalgia (15.8%) was the most common systemic reaction. One case of Guillain-barre syndrome was reported."nConclusion: Inactivated influenza vaccine administration did not result in potential adverse events in healthy adults.